Evaluating the Effectiveness of Innovative Models of Care in Family Medicine: A Comparative Analysis of Health Outcomes and Patient Satisfaction - Franco-Ariasm, Manuel; Lara, María Belén Espíndola; Torres, Lucy Maria Padilla; Jiménez, Samuel Olegario Iñiguez (South Eastern European Journal of Public Health, 2024)
Medical care in the context of family medicine has evolved with the implementation of innovative models that seek to improve health outcomes and patient satisfaction. This study evaluated the effectiveness of these models through a comparative analysis of health outcomes and patient satisfaction levels in different contexts. A comparative observational study was conducted with 200 participants divided between those who received traditional care and those under innovative models. The results indicated significant improvements in patient satisfaction and in several health indicators in the innovative models. This study suggests that the implementation of new models of care can be an effective strategy to improve care in family medicine.